2018
DOI: 10.2166/wst.2018.102
|View full text |Cite
|
Sign up to set email alerts
|

Sulphate removal from mine water with chemical, biological and membrane technologies

Abstract: Chemical, physical and biological technologies for removal of sulphate from mine tailings pond water (8 g SO/L) were investigated. Sulphate concentrations of approximately 1,400, 700, 350 and 20 mg/L were obtained using gypsum precipitation, and ettringite precipitation, biological sulphate reduction or reverse osmosis (RO) after gypsum pre-treatment, respectively. Gypsum precipitation can be widely utilized as a pre-treatment method, as was shown in this study. Clearly the lowest sulphate concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…The capacity of the weakly acidic cation exchanger for hardness ions is quite high, independent of the concentration of sodium ions in the solution. At the concentration of sodium chloride of ≈29 g/dm 3 , full exchange dynamic capacity for hardness ions in the cation exchanger DOWEX MAC-3 reaches 3,000 mg-equiv./dm 3 . Thus, DOWEX MAC-3 makes it possible to soften water effectively in order to ensure the stabilizing treatment of water before its baromembrane desalination.…”
Section: The Efficiency Of Water Softening Using Dowex Mac-3 Depenmentioning
confidence: 98%
See 4 more Smart Citations
“…The capacity of the weakly acidic cation exchanger for hardness ions is quite high, independent of the concentration of sodium ions in the solution. At the concentration of sodium chloride of ≈29 g/dm 3 , full exchange dynamic capacity for hardness ions in the cation exchanger DOWEX MAC-3 reaches 3,000 mg-equiv./dm 3 . Thus, DOWEX MAC-3 makes it possible to soften water effectively in order to ensure the stabilizing treatment of water before its baromembrane desalination.…”
Section: The Efficiency Of Water Softening Using Dowex Mac-3 Depenmentioning
confidence: 98%
“…There are many methods to purify mineralized wastewater, which include reagents-based, ion-exchange, membrane, electrochemical, biological, and others. The authors of [3] compared different methods to purify water from sulfates. It is shown that in the purification of water with the original concentration of sulfates 1,400, 700, 350, and 20 mg/dm 3 , the most effective was the reverse osmosis.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations